Micro-catchment Water Harvesting for Raising Neem in Arid Region - Gupta, G. N.; Limba, N. K.; Gupta, P. K. (Indian Forester, 1995)
The field experiment conducted on Neem raised on various types of water harvesting structures in arid region is presented.